Thermodynamic, structural, surface and transport properties of Zn-Cd liquid alloy at 800 K - K K Mishra; H K Limbu; B Yadav; A K Khan; I S Jha; D Adhikari (Bibechana, 2016)
The mixing thermodynamic and structural properties of Zn-Cd liquid at 800K has been studied using Flory’s model. To explain the mixing properties of binary liquid alloys, size factor (ф) and ordering energy (ω) are taken into account. Thermodynamic properties like free energy of mixing (GM), activity (a), Heat of mixing (HM) and entropy of mixing (SM) and the microscopic properties like concentration fluctuation in the long wave length limit (Scc(0)) and chemical short range order parameter (α1) have been calculated. Surface property has also been studied with the help of Buttler’s model. The viscosity of the melt has been computed from Kaptay equation and BBK models. Both the viscosity and surface tension of the alloy increase with addition of zinc- component.